Untreated alcohol use disorder in people who inject drugs: a major barrier to HCV treatment uptake. (13th November 2019) - Barré, T; Marcellin, F; Di Beo, V; Delorme, J; Mathurin, P; Protopopescu, C; Coste, M; Authier, N; Carrieri, P; Rolland, B
Abstract: Aims: Although people who inject drugs (PWID) are the core at-risk population in the hepatitis C (HCV) epidemic in industrialized countries, few initiate treatment. Alcohol use disorder (AUD), common within this population, has been identified as a barrier to HCV treatment uptake in the general population. We investigated whether the arrival of new and well-tolerated HCV treatments (direct-acting antivirals: DAA) has improved HCV treatment uptake in French PWID compared with former treatments (pegylated interferon-based treatments: Peg-IFN). Methods: Analyses were based on exhaustive care delivery data collected between 2012 and 2016 (study period) in the French national healthcare reimbursement database. Chronic HCV-infected individuals who received opioid agonist therapy (OAT) at least once during the study period were included. Separate analyses were performed for 2012-2013 (Peg-IFN era, 19, 700 patients) and 2014-2016 (DAA era, 22, 545 patients). Using discrete-time Cox proportional hazards models, we tested for associations between AUD (i.e. AUD-related long-term illness status, diagnosis coding during hospitalization or AUD pharmacological treatment) and first HCV treatment delivery, after adjusting for gender, age, complementary universal health cover, liver disease severity and type of OAT received. Results: Incidence rate of HCV treatment uptake per 100 person-years [95% confidence interval] was 6.56 [6.30-6.84] and 5.70 [5.51-5.89], for Peg-IFN-based treatment (2012-2013) and DAA (2014-2016), respectively. After multiple adjustment, people with AUD not receiving related medication had 30% and 14% lower Peg-IFN-based treatment and DAA uptake, respectively, than those without AUD (hazard ratio [95%CI]: 0.70 [0.62-0.80] and 0.86 [0.78-0.94]). No difference was observed between those treated for AUD and those without AUD. Conclusions: Despite the benefits of DAA, untreated AUD is still a major barrier to HCV treatment access for PWID in France. Key messages: AUD is still a barrier to HCV treatment for French PWID. DAA availability improved HCV treatment uptake for PWID with AUD.